The Effect of Creatine Monohydrate Consumption on Men's Cognitive Function with Anaerobic Exercise - -, Malha Nandika; -, Hariyanto IH; -, Willy Handoko (Universitas Negeri Semarang, 2025)
Introduction: Creatine monohydrate is a supplement used to accelerate the recovery process, increase muscle mass, and affect the cognitive function of its consumer. Objectives: This study aimed to determine the effect of consuming creatine monohydrate on male cognitive function with anaerobic exercise. Method: The methodology used in this study is by conducting experiments involving 12 participants aged between 20-45 years old with anaerobic exercise routines. The participants were asked to consume creatine monohydrate 5 gr/day for 20 days. Assessment of cognitive function was conducted on day 0 and day 21 using the XpressO by MoCA instrument, and the data were analyzed using a dependent paired t-test. Result: The average age, weight, height, and body mass index of the participants were 31.2±7.6 years old, 80.9±14.6kg, 170.6±5.1cm, and 27.8kg/m2 respectively. Significant increase in cognitive function on day 21 compared to day 0 was shown respectively by 46.75±9.8 and 32.33±9.7 (p=0.024; p<0.05). Conclusion: Creatine monohydrate consumption with a dose 5 gr/day for 20 days has an effect on the increase of male cognitive function with anaerobic exercise.